2016
DOI: 10.3390/rs8030167
|View full text |Cite
|
Sign up to set email alerts
|

The AVHRR Polar Pathfinder Climate Data Records

Abstract: With recent, dramatic changes in Arctic sea ice and the Antarctic ice sheets, the importance of monitoring the climate of the polar regions has never been greater. While many individual global satellite products exist, the AVHRR Polar Pathfinder products provide a comprehensive set of variables that can be used to study trends and interactions within the Arctic and Antarctic climate systems. This paper describes the AVHRR Polar Pathfinder (APP), which is a fundamental climate data record that provides channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 36 publications
0
62
0
Order By: Relevance
“…OTIM utilizes data from optical (visible, near-infrared, and thermal infrared) satellite instruments such as the Advanced Very High Resolution Radiometer (AVHRR) onboard National Oceanic and Atmospheric Administration (NOAA) family of Polar-orbiting Operational Environmental Satellites (POES), and is incorporated in the AVHRR Polar Pathfinder-extended (APP-x) dataset that covers the period 1982 through the present [14]. This is a very different approach than those used with ICESat, Cryosat-2, IceBridge, and SMOS.…”
mentioning
confidence: 99%
“…OTIM utilizes data from optical (visible, near-infrared, and thermal infrared) satellite instruments such as the Advanced Very High Resolution Radiometer (AVHRR) onboard National Oceanic and Atmospheric Administration (NOAA) family of Polar-orbiting Operational Environmental Satellites (POES), and is incorporated in the AVHRR Polar Pathfinder-extended (APP-x) dataset that covers the period 1982 through the present [14]. This is a very different approach than those used with ICESat, Cryosat-2, IceBridge, and SMOS.…”
mentioning
confidence: 99%
“…The mean APP-x [19] albedos of the melted and surviving parcels in this study are shown in Figure 10. The albedos in the melted populations were lower than the surviving parcel population means, which led to greater energy input for equal radiative forcing at the surface in the melted population.…”
Section: Surface Albedosmentioning
confidence: 99%
“…Downwelling shortwave and longwave radiative fluxes were obtained from the APP-x dataset [19]. Mean downwelling shortwave radiative fluxes for melted and surviving parcels were very similar for all years in the study period (Figure 8).…”
Section: Downwelling Radiative Fluxesmentioning
confidence: 99%
See 2 more Smart Citations